Experimental cardiovascular and lung researchImpact of geometric changes in a dilated aorta with a bicuspid aortic valve on blood flow disturbances – a numerical modeling study - Małota, Zbigniew; Głowacki, Jan; Kukulski, Tomasz; Sadowski, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Bicuspid aortic valve (BAV) is the most common congenital cardiac malformation that occurs in adults. Bicuspid aortic valve is strongly associated with vascular complications, such as aortic root dilatation, thoracic aortic aneurysms, and aortic dissection. This study attempted to examine the hemodynamic effect of two surgical geometry correction procedures using computer and physical modeling. The estimated changes in basic hemodynamic parameters and the possibility of reducing the risk of aortopathy and valve dysfunction can improve long-term outcomes of BAV patients. The blood flowing through the BAV generates an asymmetric, eccentric, helical flow with a significant secondary flow and increased turbulence area. Asymmetric aortic wall deformation, and the increase and redistribution of stress, may constitute the primary reasons behind endothelial damage and aortic dissection in BAV patients. The surgical correction of the dissipated aortic geometry, in contrast to the separation of the common cusp of the BAV, significantly improves the hemodynamic conditions in the ascending aorta, reduces wall stress, and eliminates the critical point of stagnation on the outer wall of the aorta. In vitro modeling methods allow for a patient-specific evaluation of hemodynamic parameters. Two parameters may be particularly helpful in evaluating the degree of aortic dilatation and the risk of aortopathy in BAV patients: the Dean number and the angle between the direction of the main stream flowing out of the valve during the mid-ejection phase and the surface of the outer wall of the aortic arch.